Perubahan Paradigma Kepemimpinan Sekolah - Thamara Safitri; Masduki Asbari; Ahlul Bae'atun Nisa; Fitri Fatmawati (Journal of Information Systems and Management (JISMA), 2023)
The purpose of writing this article is about school leadership 2.0. It explains how the thinking of a leader can change at any time including in this new era. The changes that occur cannot be separated from the rapid development of technology in all fields. The writing of this article uses a descriptive qualitative method by doing simak catat because the source of data obtained by listening to oral narratives from the Youtube channel KEMENDIKBUD RI entitled "Minister Nadiem Makarim talks about School Leadership" presented by Nadiem Anwar Makarim B.A., M.B.A. The results of this study explain that the mindset of today's leaders must be different from before because the digital revolution makes changes so fast that it cannot predict all changes but is expected to make changes with useful competencies.